Effects of Low-Speed and High-Speed Resistance Training Programs on Frailty Status, Physical Performance, Cognitive Function, and Blood Pressure in Prefrail and Frail Older Adults - Coelho-Júnior, Hélio José; Uchida, Marco Carlos (Frontiers in Medicine, 2021)
Aim: The current study investigated the effects of low-speed resistance training (LSRT) and high-speed resistance training (HSRT) on frailty status, physical performance, cognitive function and blood pressure in pre-frail and frail older people. Material and Methods: Sixty older adults, 32 prefrail and 28 frail, were randomly allocated into LSRT, HSRT, and control group (CG). Before and after intervention periods frailty status, blood pressure, heart rate, and a set of physical performance capabilities and cognitive domains were assessed. Exercise interventions occurred over 16 weeks and included 4 resistance exercises with 4-8 sets of 4-10 repetitions at moderate intensity. Results: The prevalence of frailty criteria in prefrail and frail older adults were reduced after both LSRT and HSRT. In prefrail, LSRT significantly improved lower-limb muscle strength, while mobility was only improved after HSRT. Muscle power and dual-task performance were significantly increased in both LSRT and HSRT. In frail, LSRT and HSRT similarly improved lower-limb muscle strength and power. However, exclusive improvements in dual-task were observed after LSRT. Memory was significantly increased in prefrail and frail, regardless of the type of resistance training. No significant changes were observed in blood pressure and heart rate. Conclusion: Findings of the present study indicated that both LSRT and HSRT reversed frailty status and improved physical performance in prefrail and frail older adults. However, different patterns of improvement were observed among resistance training protocols. Regarding frailty status, LSRT seemed to be more effective in reverse prefrailty and frailty when compared to HSRT. Greater improvements in muscle strength and power were also observed after LSRT, while HSRT produced superior increases in mobility and dual-task performance. Finally, resistance training programs similarly improved verbal memory in prefrail. Trial Registration: The protocol was approved by the University of Campinas Human Research Ethics Committee (Protocol No. 20021919.7.0000.5404) and retrospectively registered at ClinicalTrials.gov Protocol Registration and Results System: number to be supplied.